Network Localization of Unconscious Visual Perception in Blindsight. Issue 2 (10th January 2022) - Kletenik, Isaiah; Ferguson, Michael A.; Bateman, James R.; Cohen, Alexander L.; Lin, Christopher; Tetreault, Aaron; Pelak, Victoria S.; Anderson, Clark Alan; Prasad, Sashank; Darby, Richard Ryan; Fox, Michael D.
Abstract : Objective: Blindsight is a disorder where brain injury causes loss of conscious but not unconscious visual perception. Prior studies have produced conflicting results regarding the neuroanatomical pathways involved in this unconscious perception. Methods: We performed a systematic literature search to identify lesion locations causing visual field loss in patients with blindsight (n = 34) and patients without blindsight (n = 35). Resting state functional connectivity between each lesion location and all other brain voxels was computed using a large connectome database (n = 1, 000). Connections significantly associated with blindsight (vs no blindsight) were identified. Results: Functional connectivity between lesion locations and the ipsilesional medial pulvinar was significantly associated with blindsight (family wise error p = 0.029). No significant connectivity differences were found to other brain regions previously implicated in blindsight. This finding was independent of methods (eg, flipping lesions to the left or right) and stimulus type (moving vs static). Interpretation: Connectivity to the ipsilesional medial pulvinar best differentiates lesion locations associated with blindsight versus those without blindsight. Our results align with recent data from animal models and provide insight into the neuroanatomical substrate of unconscious visual abilities in patients. ANN NEUROL 2022;91:217–224